The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/su71215846
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Power Plants in Poland—Structure, Capacity, and Spatial Distribution

Abstract: This paper presents the analysis and evaluation of biogas power plant capacity in Poland based on the generic structure and energy production. These issues are also presented from the point of view of the obtained energy and biogas energy production in Poland against selected European Union countries. The paper also indicates a significant diversity in the spatial distribution of biogas plants in Poland. It also discusses the importance of biogas plants as one of the elements of bottom-up development of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Series production of equipment and apparatus significantly affect projects' cost reduction. Given the projected increase in the price of energy obtained by conventional methods, competitiveness of using RES will increase 9 . Different renewable sources can operate in hybrid systems, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Series production of equipment and apparatus significantly affect projects' cost reduction. Given the projected increase in the price of energy obtained by conventional methods, competitiveness of using RES will increase 9 . Different renewable sources can operate in hybrid systems, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the embargo imposed by the Russian Federation in 2014, had significant influence on Poland´s economic situation, causing the saturation of local markets with fresh agricultural products [56,57]. Thus, the farmers were recommended to use the waste as the substrate for biogas plant, because it would be profitable from the economic point of view [83]. The study conducted by Smurzyńska et al [57], with the aim to determine the biogas yield and dynamic of the fermentation process of surplus of fresh vegetables and fruits (biogas and methane productivity tests were carried out for the following vegetables and fruits: eggplants, pumpkins, cauliflower, cabbage, peppers, tomatoes, cucumbers) demonstrated that the process of methane production has not been impaired by any inhibitory factors and biogas yield obtained from individual vegetables and fruits tested was comparable.…”
Section: Fresh Fruits and Vegetables: The Controversial Casementioning
confidence: 99%
“…Many studies have been conducted to improve digestion efficiency and to enhance its economic performance. These include the design of new reactor configurations for a better digestion of a mix of different feedstocks, the running of co‐digestion using multiple feedstocks to balance nutrient conditions with the aim of enhancing biogas production, (Valenti et al ., unpublished) and upgrading raw biogas to high‐quality fuels such as biomethane, a pipeline‐quality replacement for fossil natural gas …”
Section: Introductionmentioning
confidence: 99%